Inside the Black Box of Class Size: Mechanisms, Behavioral Responses, and Social Background - Peter Fredriksson; Björn Öckert; Hessel Oosterbeek (Institute for the Study of Labor (IZA), 2014)
Studies on the effect of class size on student achievement typically find that disadvantaged students benefit more from reduced class size than others. To better understand this differential impact, we analyze changes in the learning environment due to class size, and behavioral responses to class size among parents, schools, teachers and students. The variation in class size is induced by a maximum class size rule applying to upper primary schools in Sweden. We find that in response to an increase in class size: i) teachers seem to assign more responsibility to students; ii) low-income students find their teachers hard to follow when taught in full-class iii) high-income parents help their children more with homework; iv) parents are more likely to change schools; and v) other school inputs and student effort adjust very little. These findings help explain why we find that the negative effect of class size on achievement in our data is concentrated among low-income students.
Keywords: I21; I28; J24; C31; 330; class size; social background; heterogenous effects; regression discontinuity